The Evolution of Institutional‐Research Professionals in Small‐ and Medium‐Sized Institutions. Issue 173 (July 2017) - Brown, Narren J.; Hewitt, Gordon J.; Lin, Wei‐Fang; Vater, Ruth
Abstract : This concluding chapter discusses the main challenges currently facing institutional research at small‐ and medium‐sized colleges and describes how the field may evolve.